Colonization of resistant and susceptible maize genotypes by the pink stem borer, Sesamia calamistis (Lepidoptera: Noctuidae) - Aroga, R.; Ajala, S. (2007)
The role of four colonizing responses (oviposition, larval arrest, larval establishment and larval feeding) of Sesamia calamistis (Lepidoptera:Noctuidae) in determining the resistance or susceptibility of eight genotypes of maize Zea mays L.) was elucidated. Four resistant (S59-1, 55 1 1-1, 55 27-1 and 55 27-9, two moderately resistant Tzmi 103 and Tzi 4001), and two susceptible 65 20-2 and Tzmi 407) genotypes were used in the study. S. calamistis exhibited variable colonizing responses on the maize genotypes. The interaction of the responses was also considered in order to estimate the net resistance (determined by low responses reflecting non-preference or antixenosis) or susceptibility (characterized by higher responses that promote colonization) of one genotype in comparison to another. The profiles developed from the study showed that 55 9-1 had five responses in the very low to medium range, thus confirming its resistance to S.calamistis. On the contrary, S5 20-2 had a total of four responses in the medium to very high range, while Tzmi 407 had three responses in the medium to high range and were, therefore, truly susceptible.The profiles of the other genotypes fell between these two extremes.